Bronastodobni jezičastoročajni srpi z Y-ornamentom - Pavlin, Primož (Arheološki vestnik, 1997)
Under a working title, the author deals with Bronze Age sickles typified by a Y-shaped central rib on the handle. The basic variant, variant a, has three handle ribs. The central rib splits into the form of the letter Y at the knob;one leg fuses with the back rib, another with the inner rib, which passesin an arc into a more or less pronounced blade rib (fig. 1: a). Sickles of variant a were casted in two ways; in the first, the casting point is at the knob, and in the second Urnfield period, and individual specimens in the third. They are spreaded in Transdanubia, eastern Slovenia, Croatian Zagorje, Međimurje, Slavonia, Srem, south-western Bosnia and northern Serbia. Somewhat further removed are examples from Burgenland and Lower Austria, and a sickle from Romania is very distant (fig. 4). A further 22 sickles, which differ in details from variant a, and are divided into a further 14 variants - from b-o,are presented in the appendix (fig. 1: b-o).
Keywords: archaeology; arheologija; arheološke najdbe; bronasta doba; orodje